QbD Approach to Stability Indicating HPLC Method for Estimation of Elbasvir and Grazoprevir by Green Assessment Method - Bhangale, Charushila; Somwanshi, Sachin; Kotade, Kiran; Gaikar, Mayur (Pharmaceutical Science: New Insights and Developments Vol. 2, 2025)
Introduction: Green chemistry is widely used in worldwide manufacturing, government policy, educational practice, and technology development. The main purpose of the circular economy is to establish a balance between economic growth, resource sustainability, and environmental protection. The global need to adapt procedures to meet the objectives of green analytical chemistry (GAC) is a serious challenge for the pharmaceutical industry. High-performance liquid chromatography (HPLC), one of the techniques used most commonly at various stages in the pharmaceutical industry, generates a massive volume of organic hazardous waste. Aim: To develop analytical quality by design-aided stability indicating green high-performance liquid chromatography (HPLC) method for estimation of Elbasvir and Grazoprevir in a dosage form. Materials and Methods: The percentage of ethanol in the mobile phase, flow rate, and their overall impact on the responses, such as asymmetry, theoretical plates, and resolution, were the crucial chromatographic elements that were examined in order to optimise the procedure. The primary goal of green analytical chemistry (GAC) has been to provide environmentally safe analytical techniques. Consequently, the application of GAC principles in pharmacological analysis is essential. A rotatable central composite design was used, and the Zorbax C18 column (4.6 x 150 mm, 5 µm) with 0.1% Trifluoroacetic acid and ethanol (40:60 v/v) as components of a mobile phase flowing at a rate of 1.0 ml/minute was used to create the ideal conditions for chromatographic separation with a run time of 5 minutes. At 253 nm, photodiode array detection was performed. Results: The retention times for EBS and GZP were 1.8 and 2.84 minutes, respectively. According to ICH recommendations, the proposed approach was validated, and stress tests demonstrated that Elbasvir and Grazoprevir are sensitive to acidic, basic, and oxidative stress conditions. An analytical eco-scale score evaluated the greenness profile, while a software-based evaluation. Conclusion: The developed HPLC method is eco-friendly and shall be adopted in the routine quality control of Elbasvir and Grazoprevir in a tablet dosage form. The implementation of the green strategies in the pharma analysis will provide benefits for the analysts' healthier working environment, this technique will also help commercial and industrial lab research and testing departments adopt and evaluate the various combinations in bulk and dosage forms.